Development, in-vitro and ex-vivo evaluation of HPMC E-15/Xanthan gum mucoadhesive buccal patch of telmisartan - Hattaraki Shashank Shivanand; Preethi G.B; Shashank K; Subham Roy; Suhasini Rendale (Journal of Applied Pharmaceutical Research, 2026)
Background: Telmisartan, an antihypertensive drug, exhibits poor aqueous solubility and low oral bioavailability due to extensive hepatic first-pass metabolism. Buccal delivery offers a potential alternative route to bypass first-pass metabolism and achieve sustained drug release for better blood pressure control, particularly in nocturnal hypertension. The aim of the work was to formulate and evaluate a Telmisartan mucoadhesive buccal patch for sustained drug delivery. Methodology: Telmisartan solid dispersion with Kolliphor RH 40 was prepared by solvent evaporation, and mucoadhesive buccal patches (T1–T9) were formulated by solvent casting and optimized using a 3² full factorial design with Xanthan gum (A) and HPMC E15 (B) at three levels each, followed by evaluation of physicochemical properties, mucoadhesion, swelling, drug release, permeation, and drug–excipient compatibility by FT-IR, DSC, and XRD. Results & Discussion:  Based on statistical analysis, it was observed that Xanthan gum and HPMC E15 significantly (p < 0.05) affected all the responses, and T9 was selected as the optimized formulation with a desirable swelling index of 331% and strong mucoadhesive strength of 28.5 ± 0.5 g. Optimized formulation T9 showed sustained drug release of 94.87%, and ex vivo permeation of 1.773 ± 0.033 mg/cm²) with a flux of 0.221 mg/cm²/h). Conclusion: The optimized T9 patch exhibited enhanced swelling, adhesion, sustained release, and permeation, suggesting its potential as an effective alternative for managing nocturnal hypertension.